2020
DOI: 10.2147/ott.s249353
|View full text |Cite
|
Sign up to set email alerts
|

<p>Rat Bone Marrow-Derived Mesenchymal Stem Cells Promote the Migration and Invasion of Colorectal Cancer Stem Cells</p>

Abstract: Background: Colorectal cancer is one of the most common cancers and the second leading cause of cancer-related deaths worldwide. Targeting cancer stem cells (CSCs) may be a novel strategy for the treatment of colorectal cancer. Previous studies have shown that bone marrowderived MSCs (BM-MSCs) promote tumor growth and metastasis. However, the role of rat BM-MSCs in the biological behaviors of colorectal CSCs remains unclear until now. Materials and Methods: BM-MSCs were isolated from rats and characterized. CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…Similarly, it is reported that BM-MSCs are implanted in nude mice after subcutaneous injection of HCT116-cancer stem cells (CSCs) to construct xenograft tumors. BM-MSCs can promote the migration and invasion of CSCs in CRC, suggesting that it can be a potential therapeutic target for CRC [148]. Further studies by De Boeck and colleagues found that BM-MSCs stimulate the invasion, survival, and tumorigenesis of CRC cells by releasing soluble NRG1 and activating HER2/HER3-dependent PI3K/Akt signaling cascade in CRC cells, and the high expression of NRG1 is associated with poor prognosis [149].…”
Section: Promotionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it is reported that BM-MSCs are implanted in nude mice after subcutaneous injection of HCT116-cancer stem cells (CSCs) to construct xenograft tumors. BM-MSCs can promote the migration and invasion of CSCs in CRC, suggesting that it can be a potential therapeutic target for CRC [148]. Further studies by De Boeck and colleagues found that BM-MSCs stimulate the invasion, survival, and tumorigenesis of CRC cells by releasing soluble NRG1 and activating HER2/HER3-dependent PI3K/Akt signaling cascade in CRC cells, and the high expression of NRG1 is associated with poor prognosis [149].…”
Section: Promotionmentioning
confidence: 99%
“…Interacting with CRC cells through CCL3/4/5 -CCR5 to promote the growth of CRC tumors in vivo [148] Cell-to-cell contact Promoting the EMT process of CRC through the CCL5/β-catenin/Slug pathway and SPARC [147,151] Cell-to-cell contact…”
Section: Promotionmentioning
confidence: 99%
“…Through IL-6/JAK2/STAT3 signal transduction, human CRC MSCs could increase the migration and invasion of CRC (83). Of note, rat BMSCs were found to promote the migration and invasion of CRC (84). Oh et al demonstrated that after co-culturing MSCs with CRC cells, the TGF-b1 and p53 in MSCs increased, which enhanced the invasion and proliferation of CRC (85).…”
Section: Roles Of Mesenchymal Stem Cells In Colorectal Cancermentioning
confidence: 99%
“…Through IL-6/JAK2/STAT3 signal transduction, human CRC MSCs could increase the migration and invasion of CRC ( 83 ). Of note, rat BMSCs were found to promote the migration and invasion of CRC ( 84 ). Oh et al.…”
Section: Roles Of Mesenchymal Stem Cells In Colorectal Cancermentioning
confidence: 99%
“…CD29 широко экспрессирован на различных типах клеток, включая мезенхимные и эпителиальные клетки, а также стволовые/прогениторные клетки различного происхождения [16]. Так, CD29 наряду с CD44 и CD90 зачастую рассматривается в качестве маркера мезенхимных стволовых/стромальных клеток (МСК), выделяемых из разных тканевых источников, как у человека [17], так и у грызунов [18]. Во взрослой печени интегрин β1 экспрессируют зрелые гепатоциты [19], а также печеночные стволовые клетки и гепатобласты [20].…”
Section: результаты и обсуждениеunclassified